Interchangeability of position tracking technologies; can we merge the data?. Issue 1 (2nd January 2020) - Taberner, Matt; O'Keefe, Jason; Flower, David; Phillips, Jack; Close, Graeme; Cohen, Daniel Dylan; Richter, Chris; Carling, Christopher
ABSTRACT: Purpose : The purpose of this study was to assess the interchangeability of position tracking metrics obtained using global positioning systems (GPS) versus those obtained by a semi-automatic high definition (HD) optical camera system. Methods : Data was collected from a cohort of 29 elite football players (age: 23.1 ± 5.1 years, height: 180.4 ± 5.8 cm, mass: 74.6 ± 6.7 kg) in four matches played in four different stadiums. In two matches 10 Hz GPS (GPS-1, StatSports, Belfast, UK) were used, while in the other two matches augmented 10 Hz GPS (GPS-2, StatSports, Belfast, UK) were used. All four matches were analysed concomitantly using six semi-automated HD motion cameras sampling at 25 Hz (TRACAB, Chyronhego, New York, USA). Results : Mean bias was between 6% and 10% for GPS-1 and 1–4% for GPS-2, respectively. No proportional bias was found (p > 0.184). The SEE within calibration functions (expressed in % to mean) was between 5% and 22% for GPS-1 and 4–14% for GPS-2. While some significant differences existed between GPS-1 and TRACAB (total distance and high-speed), positional tracking variables were highly correlated between GPS-1, GPS-2 and TRACAB ( r 2 > 0.92) with GPS-2 displaying stronger correlations (> r 2 = 0.96). Conclusion : In the present study augmented GPS technology (GPS-2) and the TRACAB camera system provided interchangeable measures of positional tracking metrics to allow concurrent assessment and monitoring of training and competition in football players. However, we recommend practitioners evaluate their own systems to identify where errors exist, calculate and apply the regression equations to confidently interchange data.